2020
DOI: 10.1126/science.aaw1469
|View full text |Cite
|
Sign up to set email alerts
|

A type Ia supernova at the heart of superluminous transient SN 2006gy

Abstract: Superluminous supernovae radiate up to 100 times more energy than normal supernovae. The origin of this energy and the nature of their stellar progenitors are poorly understood. We identify neutral iron lines in the spectrum of one such transient, SN 2006gy, and show that they require a large mass of iron ( 0.3 M ⊙ ) expanding at 1500 km s −1 . We demonstrate that a model of a standard Type Ia super-

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
57
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 69 publications
6
57
0
1
Order By: Relevance
“…The mergers with HG stars are much more common than mergers with CHeB stage stars. With a standard BPS simulation, we have shown that the created CSM (Figure 4) and the rate (Table 3) of CMD SN explosions in CO WD + massive star systems can be compatible with the observational constraints of SN 2006gy (Jerkstrand et al 2020) and rate of type II SLSNe.…”
Section: Co Wd and Massive Star Binaries With The Ce Evolutionsupporting
confidence: 60%
See 3 more Smart Citations
“…The mergers with HG stars are much more common than mergers with CHeB stage stars. With a standard BPS simulation, we have shown that the created CSM (Figure 4) and the rate (Table 3) of CMD SN explosions in CO WD + massive star systems can be compatible with the observational constraints of SN 2006gy (Jerkstrand et al 2020) and rate of type II SLSNe.…”
Section: Co Wd and Massive Star Binaries With The Ce Evolutionsupporting
confidence: 60%
“…They suggested one evolution pathway proposed by Sabach & Soker (2014) which is that a merger of a CO WD with the core of a red supergiant (RSG) star inside the heavy CE may generate an SN like SN 2006gy (Jerkstrand et al 2020). Following the idea of Sparks & Stecher (1974;Sabach & Soker 2014) and results of Jerkstrand et al (2020), we will study the possible progenitor model for SN 2006gy-like SLSNe with different binary physics by considering several important evolution models.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…77 We use the classifications from G. Leloudas et al (2021, in preparation) and added other luminous SNe IIn to this class. The origin of this class and its relationship to regular SNe IIn is highly debated (Gal-Yam 2012; Moriya et al 2019;Gal-Yam 2019;Jerkstrand et al 2020;Nicholl et al 2020). 78 Arcavi et al (2010); and tidal disruption events (TDEs) by Arcavi et al (2014).…”
Section: Supernova Classificationsmentioning
confidence: 99%